PENGARUH KEMITRAAN TERHADAP PENDAPATAN USAHATANI TEBU (Studi Kasus di Kecamatan Tayu Kabupaten Pati Provinsi Jawa Tengah) - Syaifun Naim; Lutfi Aris Sasongko; Eka Dewi Nurjayanti (Universitas Wahid Hasyim, 2015)
Sugar cane is one of the farming yields which is needed by sugar company as a raw material to produce sugar. Therefore, partnership between sugar cane farmer and sugar company is needed to improve the sugar cane farmer income. This research aims to describe form of a partnership between PG (Pabrik Gula) Pakis Baru with sugar cane farmer in Tayu District, to know sugar cane farmer income, and to analyze the influence of partnership to sugar cane farming income in Tayu District. The area sampling and respondents sampling conducted by purposive sampling method. Sampling area taken was Tayu District because PG Pakis Baru located at that district. Total respondent is 40 sugar cane farmers that consist of 20 sugar cane farmers who have partnership with PG Pakis Baru (partner farmers) and 20 sugar cane farmers who have not partnership with PG Pakis Baru (non-partner farmers). The land area of each respondent is limited maximum of 2 Ha. The form of partnership between PG Pakis Baru with sugar cane farmer is PG Pakis Baru played a role as avalis, which is responsible for failure risk of farmer credit repayment. Another form of partnership is PG Pakis Baru gave quota of subsidized fertilizer, technical guidance and molasses to sugar cane farmer. For partner farmers average costs is Rp25.261.110,00 and average revenue is Rp40.601.264,00, so average income is Rp14.980.154,00. For non-partner farmers average costs is Rp23.493.391,00 and average revenue is Rp33.569.741,00, so average income is Rp10.076.349,00. This result showed that income of partner farmers is higher than non-partner farmers. Based on data analysis using multiple linear regressions, partnership has a significant probability value of 0,000 means that partnership has a significant influence to sugar cane farmers income. Beside a partnership, farming costs and number of production also have a significant influence to sugar cane farmers income. While experience and farmers age had not a significant influence to sugar cane farmers income. Thus, to increase the sugar cane farming income, non-partners farmers should follow partnership program with the sugar company. While partners farmers should still run the partnership with the sugar company. Keywords: Cane, income, multiple linear regression, partnership